Enhancing Network Fault Detection with Precision Predictive AI - Dev, Deepthi Kallahakalu Vijay (International Journal of Computing and Engineering, 2024)
Traditional methods for managing and predicting faults must be revised in today's complex network landscape. Predictive Artificial Intelligence (AI) offers a proactive solution, using advanced algorithms and machine learning to analyze vast data, detect patterns, and prevent issues before they escalate. This approach significantly enhances network reliability, reduces downtime, improves operational efficiency, and has transformative potential in network management. This white paper explores this potential, providing real-world examples and integration strategies. We also discuss its benefits and challenges, highlighting its promise for ensuring stable and resilient network operations.